A lithium ion battery
By controlling the relationship between the heating rate of the lithium-ion battery and the amount of lithium-transferred electrons on the surface of the negative electrode sheet, and adjusting the composition and structure of the positive electrode and negative electrode active material layers, the lithium-ion battery is solved during the charging and discharging process. The thermal runaway problem improves the thermal safety and energy density of lithium-ion batteries.
Patent Information
- Application Number
- CN202311030746.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-08-15
AI Technical Summary
Lithium-ion batteries are prone to lithium-ion reactions during charging and discharging, resulting in thermal runaway, combustion and even explosion, reducing the thermal safety of lithium-ion batteries.
By controlling the relationship between the heating rate of the lithium-ion battery and the amount of lithium-transferred electrons on the surface of the negative electrode sheet, the lithium-ion battery discharges less heat during the charging and discharging process, reducing the risk of thermal runaway. The specific implementation method is to control the injection coefficient of the electrolyte and the compaction density of the negative electrode active material layer by adjusting the composition and structure of the positive electrode and the negative electrode active material layer.
It improves the tolerance of lithium-ion batteries to lithium-ion reactions, reduces the risk of thermal runaway, improves the thermal safety performance of lithium-ion batteries, and maintains high energy density and functional performance.
Smart Images

Figure CN116885266B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium ion battery. Background Art
[0002] With the rapid development of science and technology, lithium-ion batteries, as a high-performance, rechargeable and rechargeable battery, have the characteristics of high energy density and light weight, and are widely used in mobile devices, automobiles, energy storage and other fields. During the charging process of lithium-ion batteries, lithium ions are deintercalated from the positive electrode and embedded in the negative electrode. However, in some abnormal situations, such as insufficient lithium embedding space in the negative electrode, too much resistance to lithium ion embedding in the negative electrode, too fast lithium ion deintercalation from the positive electrode but unable to embed the same amount in the negative electrode, the lithium ions that cannot be embedded in the negative electrode can only obtain electrons on the surface of the negative electrode, thereby forming a silvery-white metallic lithium on the surface of the negative electrode, resulting in lithium precipitation. The process of lithium precipitation in lithium-ion batteries is almost inevitable. After lithium ion batteries are deintercalated, the metallic lithium deposited on the surface of the negative electrode is prone to side reactions with the electrolyte and release a large amount of heat, which leads to thermal runaway, combustion and even explosion of lithium-ion batteries, making the thermal safety of lithium-ion batteries poor. Summary of the invention
[0003] In order to solve the above-mentioned defects in the prior art, the purpose of the present invention is to provide a lithium ion battery, which has a certain tolerance to lithium plating reaction, can reduce the risk of thermal runaway of the lithium ion battery, and improve the thermal safety performance of the lithium ion battery.
[0004] The technical solution provided according to the purpose of the present invention is as follows:
[0005] A lithium-ion battery, comprising:
[0006] A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector;
[0007] A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector;
[0008] The relationship between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode sheet y satisfies 0.02℃ / (min·mAh)≤y≤0.033℃ / (min·mAh);
[0009] in, T1 is the self-heating temperature of the lithium-ion battery, in °C, T2 is the thermal runaway temperature of the lithium-ion battery, in °C, △t is the time required for the lithium-ion battery to rise from the self-heating temperature to the thermal runaway temperature, in min, and A is the amount of electrons transferred from lithium deposition on the surface of the negative electrode, in mAh.
[0010] The present invention controls the relationship between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode, so that the lithium-ion battery releases less heat during the charging and discharging process and is not prone to thermal runaway, thereby improving the tolerance of the lithium-ion battery to the lithium deposition reaction and improving the thermal safety of the lithium-ion battery. At the same time, the lithium-ion battery also has higher energy density and functional performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is the DSC spectra of Example 1 and Example 5;
[0012] Figure 2 This is the DSC spectrum of Comparative Example 1. DETAILED DESCRIPTION
[0013] For better understanding and implementation, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0014] In the description of the present invention, it should be noted that the terms "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc. indicating directions or positional relationships are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.
[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0016] In the present invention, PVDF is polyvinylidene fluoride, NMP is N-methylpyrrolidone, CMC is carboxymethyl cellulose, SBR is styrene-butadiene rubber, EC is ethylene carbonate, EMC is ethyl methyl carbonate, DEC is diethyl carbonate, and DMC is dimethyl carbonate.
[0017] The filling coefficient is the electrolyte injection mass corresponding to unit capacity, and the unit of the filling coefficient is g / Ah.
[0018] Example 1
[0019] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0020] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0021] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, stir it under the action of a vacuum mixer until the system is uniform, and obtain the negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode active material layer with a compaction density of 1.66g / cm 3 The negative electrode.
[0022] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0023] 4) Battery preparation: stack the positive electrode sheet, polyethylene separator and negative electrode sheet of step 1) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and obtain a lithium-ion battery with a liquid injection coefficient of 2.3g / Ah in this embodiment through vacuum packaging, standing, forming, shaping and other processes.
[0024] Example 2
[0025] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0026] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32 O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0027] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, stir it under the action of a vacuum mixer until the system is uniform, and obtain the negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode active material layer with a compaction density of 1.68g / cm 3 The negative electrode.
[0028] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0029] 4) Battery preparation: stack the positive electrode sheet, polyethylene separator and negative electrode sheet of step 1) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and go through vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery with an injection coefficient of 2.2g / Ah in this embodiment.
[0030] Example 3
[0031] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0032] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32 O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0033] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, and stir it under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, followed by cold pressing and slitting to obtain a negative electrode active material layer with a compaction density of 1.70g / cm 3 The negative electrode.
[0034] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0035] 4) Battery preparation: stack the positive electrode sheet, polyethylene separator and negative electrode sheet of step 1) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and go through vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery with an injection coefficient of 2.1g / Ah in this embodiment.
[0036] Example 4
[0037] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0038] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32 O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0039] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, stir it under the action of a vacuum mixer until the system is uniform, and obtain the negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode active material layer with a compaction density of 1.72g / cm 3 The negative electrode.
[0040] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0041] 4) Battery preparation: stack the positive electrode sheet, polyethylene separator and negative electrode sheet of step 1) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and go through vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery with an injection coefficient of 2.0g / Ah in this embodiment.
[0042] Example 5
[0043] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0044] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32 O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0045] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, stir it under the action of a vacuum mixer until the system is uniform, and obtain the negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode active material layer with a compaction density of 1.74g / cm 3 The negative electrode.
[0046] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0047] 4) Battery preparation: stack the positive electrode sheet, polyethylene separator and negative electrode sheet of step 1) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and go through vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery with an injection coefficient of 1.9g / Ah in this embodiment.
[0048] Comparative Example 1
[0049] This comparative example provides a method for preparing a lithium ion battery, comprising the following steps:
[0050] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32 O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0051] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, and stir it under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, followed by cold pressing and slitting to obtain a negative electrode active material layer with a compaction density of 1.73g / cm 3 The negative electrode.
[0052] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0053] 4) Battery preparation: stack the positive electrode sheet of step 1), the polyethylene separator, and the negative electrode sheet of step 2) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and undergo vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery with an injection coefficient of 2.5g / Ah in this comparative example.
[0054] Comparative Example 2
[0055] This comparative example provides a method for preparing a lithium ion battery, comprising the following steps:
[0056] 1) Preparation of positive electrode sheet: LiNi 0.56 Co 0.12 Mn 0.32 O2, conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and then solvent NMP is added to the mixture, and the mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil to form a positive electrode active material layer, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0057] 2) Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR in a mass ratio of 96.4:1:1.2:1.4, then add the solvent deionized water to the mixture, and stir it under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the opposite surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and then dried at room temperature and transferred to an oven for drying, followed by cold pressing and slitting to obtain a negative electrode active material layer with a compaction density of 1.71g / cm 3 The negative electrode.
[0058] 3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then an inorganic film-forming additive CO2 and a sufficiently dried lithium salt LiPF6 are added to the organic solvent, and stirred until completely dissolved to obtain an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0059] 4) Battery preparation: stack the positive electrode sheet of step 1), the polyethylene separator, and the negative electrode sheet of step 2) in order, so that the polyethylene separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain a bare battery cell. Place the bare battery cell in a shell, inject electrolyte after drying, and undergo vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery with an injection coefficient of 2.4g / Ah in this comparative example.
[0060] Table 1 shows the parameter characteristics during the preparation of lithium-ion batteries of Examples 1-5 and Comparative Examples 1-2.
[0061] Table 1
[0062]
[0063]
[0064] Performance testing and analysis
[0065] 1. Test object: lithium ion batteries prepared in Examples 1-5 and Comparative Examples 1-2.
[0066] 2. Test items
[0067] 1) Lithium deposition test
[0068] Three groups of lithium-ion batteries of Examples 1-5 and Comparative Examples 1-2 produced in the same batch were prepared. The three groups of lithium-ion batteries were all charged at a constant current and constant voltage of 1.4C to an upper limit voltage of 4.35V, left standing for 30 minutes, and discharged at a constant current of 1C to a lower limit voltage of 2.75V, left standing for 30 minutes, to perform a charge and discharge cycle test for 100 cycles.
[0069] 2) Lithium deposition test - isopropanol method
[0070] The lithium-ion batteries of the first group of Examples 1-5 and Comparative Examples 1-2 after lithium deposition were all discharged at a rate of 0.05C to an empty state and then disassembled. Then, the lithium deposition areas on the negative electrode surfaces of Examples 1-5 and Comparative Examples 1-2 after disassembly were respectively placed in a sealed container filled with isopropanol. According to the chemical reaction equation Li+(CH3)2CH2OH=(CH3)2CH2OLi+1 / 2H2, the active metal lithium reacted with the isopropanol to generate hydrogen. According to the ideal gas equation PV=nRT, the amount of hydrogen was calculated by the change in pressure before and after the reaction, thereby calculating the amount of metal lithium deposited on the negative electrode surface. Before the reaction, P 前 V=n 前 RT, after reaction, P 后 V=n 后 RT, hence Under standard conditions, the volume of 1 mol of air is about 22400 mL. The number of moles of air in the sealed container before the reaction is Therefore, the number of moles of the mixed gas in the closed container after the reaction is Since the gas in the sealed container after the reaction is a mixture of air and hydrogen, and the air does not participate in the reaction, the number of moles of air remains unchanged, and the number of moles of hydrogen is Then the number of moles of active metal lithium is
[0071] In lithium-ion batteries, the complete deintercalation of 1 mol of lithium ions will transfer the charge of 1 mol of electrons, that is, 96500C, which is equal to 1F. Therefore, n 锂 The amount of electricity required for complete lithium ion deintercalation and transfer is nF, with the unit of C. If it is converted to mAh, the amount of electricity required for lithium deposition and transfer of electrons on the surface of the negative electrode is A=nF / 3.6C, with the unit of mAh.
[0072] 3) Lithium-ion battery thermal stability test
[0073] The lithium-ion batteries after lithium precipitation in the second group of Examples 1-5 and Comparative Examples 1-2 were all charged at 25°C at a constant current rate of 1 / 3C to the upper limit voltage of the fully charged state, and then switched to constant voltage charging until the current was less than 0.05C, and left to stand for 30 minutes. Then, the surfaces of the fully charged lithium-ion batteries in Examples 1-5 and Comparative Examples 1-2 after lithium precipitation were evenly wrapped with heating wires and placed in an adiabatic accelerating calorimeter (ARC) for adiabatic thermal stability test until the battery had thermal runaway and the test ended. Among them, when the heating rate of the lithium-ion battery reaches 0.02°C / min, the temperature of the lithium-ion battery at this time is the self-heating temperature, represented by T1, and the unit is °C. When the heating rate of the lithium-ion battery reaches 1°C / min, the temperature of the lithium-ion battery at this time is the thermal runaway temperature, represented by T2, and the unit is °C. The time required for the lithium-ion battery to rise from the self-heating temperature to the thermal runaway temperature is represented by △t, and the unit is min.
[0074] The definition y represents the relationship between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode. Its unit is ℃ / (min·mAh).
[0075] 4) Thermal stability test of positive and negative active materials of lithium-ion batteries
[0076] The lithium-ion batteries of the third group of Examples 1-5 and Comparative Examples 1-2 after lithium deposition were all charged at 1 / 3C constant current at 25°C to the upper limit voltage of the fully charged state, then switched to constant voltage charging until the current was less than 0.05C, and left to stand for 30 minutes. The fully charged lithium-ion batteries of Examples 1-5 and Comparative Examples 1-2 after lithium deposition were disassembled, and the disassembled positive and negative electrodes were cleaned with DMC to remove the residual electrolyte on the surface, dried, and then the positive electrode active material on the surface of the positive electrode and the negative electrode active material on the surface of the negative electrode were scraped off.
[0077] The heat release of the positive and negative active materials was tested using a differential scanning calorimeter (DSC). The positive and negative active materials were placed in a high-pressure crucible at a mass ratio of 1:1.1 and separated by a polyethylene diaphragm. Then, an electrolyte equivalent to 1.4 times the total mass of the positive and negative active materials was injected into the high-pressure crucible and heated at a heating rate of 5°C / min until the temperature rose to 400°C. The experiment ended. The heat release Q per unit mass of the positive and negative active materials was obtained using the DSC spectrum in J / g.
[0078] 3. Test results: See Table 2.
[0079] Table 2
[0080]
[0081] From Table 2, Figure 1 and Figure 2It can be seen that the maximum heat release of the positive and negative active materials of the lithium ion batteries of Examples 1-5 does not exceed 2328 J / g, which is significantly lower than the heat release of the positive and negative active materials of the lithium ion batteries of Comparative Examples 1-2 (2686 J / g and 3615 J / g), indicating that the lithium ion batteries of Examples 1-5 have a high tolerance to lithium precipitation reactions, have high thermal safety, and the risk of thermal runaway of the lithium ion batteries during use is low.
[0082] Comparing the test results of Examples 1-5 and Comparative Examples 1-2, it can be seen that the thermal safety of the lithium-ion battery of Examples 1-5 is better than that of Comparative Examples 1-2 because the relationship y between the heating rate of the lithium-ion battery of Examples 1-5 and the amount of electrons transferred by lithium deposition on the surface of the negative electrode sheet satisfies the following condition: 0.02°C / (min·mAh)≤y≤0.033°C / (min·mAh). Within this range, the heating rate of the lithium-ion battery is small, the heat release is small, the lithium-ion battery is not prone to thermal runaway, and the compacted density of the negative electrode active material layer of the lithium-ion battery is 1.4g / cm 3 -1.74g / cm 3 The compaction density is moderate, which will not be too large to cause cracking of the active material layer or crushing of the active material particles, nor too small to cause excessive thickness of the lithium-ion battery, so that the lithium-ion battery has better energy density and power performance. In comparative example 1, the y value is too small, resulting in excessive heat release of the lithium-ion battery, reduced thermal safety performance of the lithium-ion battery, and easy thermal runaway. In comparative example 2, the y value is too large, the lithium-ion battery releases a large amount of heat, and thermal runaway is prone to occur and spreads rapidly.
[0083] Furthermore, the thermal safety of the lithium-ion batteries of Examples 3-5 is better than that of Examples 1-2, indicating that the relationship between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode sheet is preferably in the range of 0.026°C / (min·mAh)≤y≤0.031°C / (min·mAh). More preferably, 0.026°C / (min·mAh)≤y≤0.027°C / (min·mAh).
[0084] Referring to Table 1 and Table 2, the thermal safety performance of the lithium ion batteries of Examples 1-5 and Comparative Examples 1-2 is analyzed in combination with the preparation method. It can be seen that the compaction density of the negative electrode active material layer is 1.4 g / cm 3 -1.74g / cm 3range, and the injection coefficient is within the range of 1.9g / Ah-2.3g / Ah, which is conducive to improving the thermal safety performance of lithium-ion batteries. This is because the compaction density of the negative electrode active material layer and the electrolyte content cooperate to affect the degree of electrolyte wetting of the negative electrode sheet and the reaction activity of the active metal lithium and the electrolyte, thereby affecting the heat release and heat release rate of the lithium-ion battery. Specifically, when the negative electrode active material layer has a higher compaction density, the degree of electrolyte wetting of the negative electrode sheet is relatively low, and the side reaction of the active metal lithium and the electrolyte is weak, so the heat release is small. When the injection coefficient is small, the electrolyte content is small, and the degree of electrolyte wetting of the positive and negative electrode sheets is low, so that the positive and negative active materials participating in the reaction are less, and the heat generation is relatively reduced. For comparative examples 1-2, it has a higher injection coefficient, resulting in the electrolyte having better wettability to the positive and negative electrode sheets, so that the positive and negative active materials participating in the reaction are significantly increased, thereby increasing the heat generation, resulting in a decrease in the thermal safety of the lithium-ion battery.
[0085] In addition, although the lithium-ion battery of the present invention generates less heat when the injection coefficient is low, when the injection coefficient is too low, for example, less than 1.9g / Ah, it will make it difficult for the electrolyte to infiltrate the positive and negative electrodes, and the lithium ion deintercalation ability will be greatly reduced. At the same time, the charge transfer impedance at the interface between the positive and negative electrodes and the electrolyte will be significantly increased, thereby reducing the capacity of the lithium-ion battery. When the compaction density of the negative electrode active material layer is lower than 1.4g / cm 3 When the negative electrode sheet is thicker, the volume energy density of the lithium-ion battery is lower; when the compaction density of the negative electrode active material layer is higher than 1.74g / cm 3 When the negative electrode active material layer is easily cracked or the negative electrode active material particles are easily broken, the negative electrode active material is easily fallen off, so that the capacity of the lithium ion battery is reduced.
[0086] Furthermore, the thermal safety of the lithium-ion batteries of Examples 3-5 is better than that of Examples 1-2, indicating that the compaction density of the negative electrode active material layer is preferably selected to be 1.56 g / cm 3 -1.74g / cm 3 The injection coefficient is preferably selected in the range of 1.9 g / Ah-2.1 g / Ah. More preferably, the compaction density of the negative electrode active material layer is 1.64 g / cm 3 -1.74g / cm 3 Within the range, the injection coefficient is in the range of 1.9g / Ah-2.0g / Ah.
[0087] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above-mentioned implementation mode, but also include technical schemes composed of any combination of the above-mentioned technical features. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: include: A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; The relationship y between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode sheet satisfies 0.02°C / (min·mAh)≤y≤0.033°C / (min·mAh); in, T1 is the self-heating temperature of the lithium-ion battery, in °C, T2 is the thermal runaway temperature of the lithium-ion battery, in °C, Δt is the time required for the lithium-ion battery to rise from the self-heating temperature to the thermal runaway temperature, in min, and A is the amount of electrons transferred by lithium deposition on the surface of the negative electrode, in mAh; The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is LiNi x Co y Mn (1-x-y) O2, where 0<x<1, 0<y<1, 0<x+y<1; The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is graphite; The compaction density of the negative electrode active material layer is 1.4 g / cm 3 -1.74g / cm 3 ; The lithium-ion battery also includes an electrolyte, and the electrolyte injection coefficient is 1.9g / Ah-2.3g / Ah.
2. A lithium ion battery according to claim 1, characterized in that: The relationship y between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode sheet satisfies 0.026°C / (min·mAh)≤y≤0.031°C / (min·mAh).
3. A lithium ion battery according to claim 1 or 2, characterized in that: The relationship y between the heating rate of the lithium-ion battery and the amount of electrons transferred by lithium deposition on the surface of the negative electrode sheet satisfies 0.026°C / (min·mAh)≤y≤0.027°C / (min·mAh).
4. A lithium ion battery according to claim 1, characterized in that: The compaction density of the negative electrode active material layer is 1.70 g / cm 3 -1.74g / cm 3 .
5. A lithium ion battery according to claim 1, characterized in that: The electrolyte injection coefficient is 1.9g / Ah-2.1g / Ah.
Citation Information
Patent Citations
Quick-charge long-cycle and low-temperature and high discharge capacity cylindrical lithium ion battery
CN110600696A